Relationships between inherent optical properties and the depth of penetration of solar radiation in optically complex coastal waters. Issue 5 (7th May 2013) - Cunningham, Alex; Ramage, Leanne; McKee, David
Abstract : [1] The attenuation of downward planar irradiance can be quantified by K ¯ d ( E 10 %, λ ), the diffuse attenuation coefficient calculated from the surface to the depth where the irradiance Ed at wavelength λ falls to 10% of its surface value. Theoretical studies by Gordon (1989) and Lee et al. (2005a) suggest that K ¯ d ( E 10 %, λ ) can be derived from the absorption coefficient, a ( λ ) and the backscattering coefficient, bb ( λ ), using equations incorporating either the solar zenith angle ( θa ) or the subsurface distribution function ( D 0 ) and empirical coefficients derived by radiative transfer modeling. These results have not, however, been validated against in situ measurements. We have therefore assessed the performance of both models using measurements of a ( λ ), bb ( λ ), and K ¯ d ( E 10 %, λ ) for 100 stations in UK coastal waters. Best results were obtained from the Lee et al. (2005a) model, for which over 90% of the predicted K ¯ d ( E 10 %, λ ) values in the 440 nm to 665 nm range were within ±0.1 m −1 of those measured in situ. A strong linear relationship ( R 2 > 0.95, mean relative difference 5.4%) was found between K ¯ d ( E 10 % ) at 490 nm and the reciprocal of the depth of the midpoint of the euphotic zone ( z 10%, PAR). This allowed ( z 10%, PAR) to be predicted from measured values of a (490 nm), bb (490 nm) and θa, using the Lee et al. model as an intermediate step, with an RMS error of 1.25 m over the 2.5–25.0 m range covered by our data set. Key Points: Diffuse attenuation coefficient models assessed using in situ measurements Euphotic depths linked to inherent optical properties Predictive equations derived